Critical biogeochemical functions in the subsurface are associated with bacteria from new phyla and little studied lineages. (22nd July 2015) - Hug, Laura A.; Thomas, Brian C.; Sharon, Itai; Brown, Christopher T.; Sharma, Ritin; Hettich, Robert L.; Wilkins, Michael J.; Williams, Kenneth H.; Singh, Andrea; Banfield, Jillian F.
Summary: Nitrogen, sulfur and carbon fluxes in the terrestrial subsurface are determined by the intersecting activities of microbial community members, yet the organisms responsible are largely unknown. Metagenomic methods can identify organisms and functions, but genome recovery is often precluded by data complexity. To address this limitation, we developed subsampling assembly methods to re‐construct high‐quality draft genomes from complex samples. We applied these methods to evaluate the interlinked roles of the most abundant organisms in biogeochemical cycling in the aquifer sediment. Community proteomics confirmed these activities. The eight most abundant organisms belong to novel lineages, and two represent phyla with no previously sequenced genome. Four organisms are predicted to fix carbon via the Calvin–Benson–Bassham, Wood–Ljungdahl or 3‐hydroxyproprionate/4‐hydroxybutarate pathways. The profiled organisms are involved in the network of denitrification, dissimilatory nitrate reduction to ammonia, ammonia oxidation and sulfate reduction/oxidation, and require substrates supplied by other community members. An ammonium‐oxidizing Thaumarchaeote is the most abundant community member, despite low ammonium concentrations in the groundwater. This organism likely benefits from two other relatively abundant organisms capable of producing ammonium from nitrate, which is abundant in the groundwater. Overall, dominant members of the microbial community are interconnected through exchange of geochemical resources.